Analisis Konsep Dasar Manajemen Sumber Daya Manusia - Putra, Vebri Pradinata; A., Faizal; Putri, Tama Erlanda; Wulandari, Sri; Afriza, Afriza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The aim of this research is to analyze the main challenges in human resource management in Indonesia and identify relevant solutions to support sustainable economic growth and inclusive organizational development. This research uses a qualitative approach or library research and field research. This research found that the gap in qualifications between college graduates and the needs of the job market is a major challenge in human resource management in Indonesia, so adjustments to the education curriculum are needed. Women's workforce participation is still low due to cultural barriers and unfairness in the distribution of work, so organizations need to develop policies that support gender equality. Non-transparent performance evaluation is a significant problem and needs to be addressed with an evidence-based system. Lack of access to training and career development hinders employee progress, especially in remote sectors, necessitating investment in career development programs. Inconsistency in the application of labor law creates uncertainty, so consistency in its application is needed. Diversity of cultures, religions and ethnic backgrounds requires inclusive HR management to avoid discrimination. Adaptation to technological change is crucial, with digital skills and adaptability increasingly important. Organizations and governments need to collaborate to prepare the workforce for the era of digitalization through relevant training and technological accessibility.